2006
DOI: 10.1016/j.rmed.2006.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for noninvasive ventilation in acute respiratory distress syndrome? A meta-analysis

Abstract: The role of noninvasive ventilation (NIV) in the management of acute respiratory distress syndrome (ARDS) is controversial. The aim of this study was to assess the effect of NIV on the rate of endotracheal intubation and intensive care unit (ICU) mortality in patients with ARDS. We searched the MEDLINE database for relevant studies published from 1980 to September 2005, and included studies if (a) the design was a randomized controlled trial; (b) patients had ARDS irrespective of the underlying etiology; (c) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 9 publications
4
48
0
7
Order By: Relevance
“…16 A meta-analysis suggested that NIV did not decrease the intubation rate and that there was not enough evidence to support the use of NIV in ALI/ARDS patients. 18 Recent research suggests that NIV benefits a small percentage of patients with ALI/ARDS due to H1N1, but the past high NIV failure rate should be kept in mind, and these patients should be closely monitored and intubated without delay if they clinically deteriorate. 19 The H1N1 pandemic differed from earlier pandemics such as the H2N2 1889 Russian influenza pandemic, the H2N2 1957 Asian influenza pandemic, and the H3N2 1968 Hong Kong influenza pandemic, in which the infection was mostly among children and young adults, and the mortality was greatest in very young children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…16 A meta-analysis suggested that NIV did not decrease the intubation rate and that there was not enough evidence to support the use of NIV in ALI/ARDS patients. 18 Recent research suggests that NIV benefits a small percentage of patients with ALI/ARDS due to H1N1, but the past high NIV failure rate should be kept in mind, and these patients should be closely monitored and intubated without delay if they clinically deteriorate. 19 The H1N1 pandemic differed from earlier pandemics such as the H2N2 1889 Russian influenza pandemic, the H2N2 1957 Asian influenza pandemic, and the H3N2 1968 Hong Kong influenza pandemic, in which the infection was mostly among children and young adults, and the mortality was greatest in very young children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Independent risk factors for NPPV failure in this group of patients include severe hypoxaemia, shock and metabolic acidosis [64]. A recent meta-analysis reported no reduction in the ETI rate and ICU mortality rate with the addition of NPPV to standard care [66]. Conclusions are difficult to draw owing to the heterogeneity of the studies analysed.…”
Section: Acute Cardiogenic Pulmonary Oedemamentioning
confidence: 96%
“…20 However, because of substantial patient heterogeneity in the included studies, that result cannot be extrapolated to the subset of patients with ALI and ARDS. Agarwal et al 21 conducted a meta-analysis of randomized controlled trials and included only patients with ALI/ARDS. The results suggested that patients with ALI/ARDS were unlikely to have important outcome benefits from NIV added to standard therapy, but the analysis included only 3 studies (with a total of 111 patients), so there was a chance of type I and type II errors.…”
Section: Physiological Rationalementioning
confidence: 99%